PK2/PKR1 Signaling Regulates Bladder Function and Sensation in Rats with Cyclophosphamide-Induced Cystitis - Biao Chen; Huiping Zhang; Lili Liu; Jiaojiao Wang; Zhangqun Ye (Hindawi Limited, 2015)
Prokineticin 2 (PK2) is a novel chemokine-like peptide with multiple proinflammatory and nociception-related activities. This study aimed to explore the potential role of PK2 in modulating bladder activity and sensation in rats with cyclophosphamide- (CYP-) induced cystitis. Changes of PK2 and prokineticin receptors (PKRs) in normal and inflamed urinary bladders were determined at several time points (4 h, 48 h, and 8 d) after CYP treatment. Combining a nonselective antagonist of prokineticin receptors (PKRA), we further evaluated the regulatory role of PK2 in modulating bladder function and visceral pain sensation via conscious cystometry and pain behavioral scoring. PK2 and prokineticin receptor 1 (PKR1), but not prokineticin receptor 2, were detected in normal and upregulated in CYP-treated rat bladders at several levels. Immunohistochemistry staining localized PKR1 primarily in the urothelium. Blocking PKRs with PKRA showed no effect on micturition reflex activity and bladder sensation in control rats while it increased the voiding volume, prolonged voiding interval, and ameliorated visceral hyperalgesia in rats suffering from CYP-induced cystitis. In conclusion, PK2/PKR1 signaling pathway contributes to the modulation of inflammation-mediated voiding dysfunction and spontaneous visceral pain. Local blockade of PKRs may represent a novel and promising therapeutic strategy for the clinical management of inflammation-related bladder diseases.